Development of Intertextual-Based Learning Videos on Corrosion Concept - Rachmawati, Nabilla Novia; Wiji, Wiji; Mulyani, Sri (Jurnal Inovasi Pembelajaran Kimia, 2025)
This study aimed to develop and evaluate an intertextual-based instructional video on the topic of corrosion by integrating macroscopic, submicroscopic, and symbolic representations within a constructivist multimedia framework. The development followed the ADDIE model through five stages: analysis, design, development, implementation, and evaluation. The video, divided into three segments—corrosion process, prevention methods, and influencing factors—was validated by experts in content, pedagogy, and media. Validation results showed high feasibility with scores of 84.2% (content), 93.75% (pedagogy), and 88.86% (media), all categorized as “Very Good.” Teacher responses averaged 97.29%, while student responses reached 100%, indicating excellent clarity, contextual relevance, and engagement. Minor revisions related to narration and animation sequencing were implemented based on expert feedback. The main innovation of this study lies in combining intertextual contexts with multilevel chemical representations to make abstract electrochemical processes more accessible. The developed video is feasible for use as a teaching aid in electrochemistry and has potential for adaptation to other chemistry topics requiring multiple representations.